Sodium variation in Geminid meteoroids from (3200) Phaethon. (December 2020) - Abe, Shinsuke; Ogawa, Takumi; Maeda, Koji; Arai, Tomoko
Abstract: Sodium is a perfect indicator to investigate the volatility within meteoroid composition. Spectroscopic observations of the Geminid meteors were carried out using modern high sensitive large format CMOS cameras. 149 visible spectra of the Geminid meteors observed in 2017 and 2018 were analyzed by a newly developed procedure. The variation of Na, Mg and Fe during meteor ablation in the atmosphere has been studied. Although sodium is depleted in ~ 80% of the Geminids, statistically significant variations of sodium in the Geminid meteors were found. It should be noted that Na depletion in the Geminid meteors increased with decreasing meteoroid size. A yearly variation of Na in the Geminid meteor streams was also found. Solar-heating age across the different parts of the meteoroids stream ejected from a parent active asteroid (3200) Phaethon having 0.14 AU small perihelion distance seems to the most likely explanation for the sodium variation and depletion. Surprisingly, three iron Geminid meteors were detected across the maximum of 2018 Geminids. Highlights: 149 visible spectra of the Geminid meteors in 2017 and 2018 were observed by using modern high sensitive large format CMOS cameras with a newly developed procedure. Although sodium is depleted in ~80 % of the Geminids, tatistically significant variations of sodium in the Geminid meteors were found. Solar-heating age across the different parts of the meteoroids stream ejected from a parent active asteroid (3200) Phaethon having 0.14 AU small perihelion distance seems to the most likely explanation for the sodium variation and depletion. Three iron Geminid meteors were also detected across the maximum of 2018 Geminids.